PENGARUH KEPEMILIKAN KELUARGA TERHADAP TAX AVOIDANCE DENGAN KUALITAS AUDIT SEBAGAI VARIABEL MODERATING - Windy Maharani; Agung Juliarto (Diponegoro Journal of Accounting, 2019)
Tax avoidance is problem that unique and complex so its important to be investigated. This research aims to examine and find the empirical evidences about the effect of family ownership and audit quality to corporate tax avoidance. It also investigates whether audit quality affect on family ownership and corporate tax avoidance. Tax avoidance in this research is proxied by using the Effective Tax Rate (ETR). The population of this research was non-financial companies which listed on the Indonesian Stock Exchange (IDX) on the year 2015 – 2017 with a total sampel of 143. The method of data collection used in this study was purposive sampling method. There are two control variables include in this study, leverage and size. Multiple linear regression analysis was used as the primary tool of analysis in this research. The result of this study indicate that the family ownership does not have a significant influence to the corporate tax avoidance. Audit quality has significant influence on corporate tax avoidance, but audit quality as moderating variabel does not have moderating effect on the relationship between family ownership and tax avoidance.